2021
DOI: 10.48550/arxiv.2103.13715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple Orthogonal Polynomials and Random Walks

Amílcar Branquinho,
Ana Foulquié-Moreno,
Manuel Mañas
et al.

Abstract: A. Given a non-negative Jacobi matrix describing higher order recurrence relations for multiple orthogonal polynomials of type II and corresponding linear forms of type I, a general strategy for constructing a pair of stochastic matrices, dual to each other, is provided. The corresponding Markov chains (or 1D random walks) allow, in one transition, to reach for the 𝑁-th previous states, to remain in the state or reach for the immediately next state. The dual Markov chains allow, in one transition, to reach fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…Karlin and McGregor themselves [13] and others [14,15,16,17] used multivariate orthogonal polynomials to analyze multidimensional or composition BDP. For applications of matrix orthogonal polynomials to quasi-birth and death processes one may consult [18] or [19,20] in the discrete time case and again for discrete time, random walks that multiple polynomials entail have been looked at recently in [21].…”
Section: Introductionmentioning
confidence: 99%
“…Karlin and McGregor themselves [13] and others [14,15,16,17] used multivariate orthogonal polynomials to analyze multidimensional or composition BDP. For applications of matrix orthogonal polynomials to quasi-birth and death processes one may consult [18] or [19,20] in the discrete time case and again for discrete time, random walks that multiple polynomials entail have been looked at recently in [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we continue our investigations on random walk orthogonal polynomials of multiple type. In our previous paper [15] we found that the ideas of Karlin and McGregor [33], see also [31,32], can be extended from standard orthogonality to the multiple orthogonality scenario, whenever the Jacobi matrix is nonnegative and bounded. Now, instead of birth and death Markov chains, in which the non zero transition probabilities could only happen for near neighbors, we have that transitions to the 𝑁-th previous states are permitted.…”
mentioning
confidence: 99%
“…In [15] we presented the Jacobi-Piñeiro multiple orthogonal polynomials as a case study, and several properties were given. In particular, we showed the region where the Jacobi-Piñeiro random walks were recurrent or transient in terms of the Jacobi-Piñeiro parameters.…”
mentioning
confidence: 99%
See 2 more Smart Citations

Hypergeometric Multiple Orthogonal Polynomials and Random Walks

Branquinho,
Fernández-Díaz,
Foulquié-Moreno
et al. 2021
Preprint
Self Cite